A Travel Advice Issued By The Department Of Foreign Affairs And Trade Of Australia (A Political Vehicle) - slamet riyadi (Jurnal Lingua Idea, 2016)
This critical discourse analysis tried to reveal that a discourse is never neutral, even though it tends to become normative with repetitive use. In this case revealing the social problems and power relations exist in a part of advice issued by the Department of Foreign Affairs and Trade of Australia, and also the ideology represented, the intertextuality, and the connections between social and cultural structures that may exists become the aims of the analysis . The analysis using CDA proved that the advice issued by the Department of Foreign Affairs and Trade of Australia may means 1) there was an exercise of power from the authority to its citizens, 2) The ideology of terrorist threat which existed in parts of the text served as a black campaign for Indonesia, and 3) the discourse also challenged the Australian Identity especially for the Aborigine.